Recovery from Adolescent Anorexia Nervosa and Associations with Diurnal Patterns of Salivary Stress Hormones: A Case Report - Oskis, Andrea; Loveday, Catherine; Hucklebridge, Frank; Wood, David; Clow, Angela (Case Reports in Psychiatry, 2012)
In the neurodevelopment of adolescent anorexia nervosa (AN), dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis is proposed to be a central component. Furthermore, a therapeutic milieu focusing on affect regulation can contribute much to treatment, given the emotional processing difficulties associated with this disorder. Studies of HPA axis function following such specialist treatments for adolescent AN, however, are rare. This study describes the diurnal pattern of HPA axis activation, including the cortisol awakening response (CAR), in a 16-year-old female diagnosed with AN both during illness and at clinical recovery following milieu therapy with a focus on affect regulation. Specialised single-case study statistics were used to assess whether the patient's data were significantly different from the healthy “norm” at illness and recovery. During illness, her measure of affective problems was outside of the normal range and cortisol and DHEA secretory profiles were significantly elevated across the diurnal period. However, at recovery both her affective state and HPA axis function became comparable to healthy controls. This case study suggests that salivary markers of HPA axis function can be feasibly incorporated into the clinical regime within a specialist adolescent AN residential service and could be used by clinicians to monitor prognosis and interventions.